2015
DOI: 10.1038/srep09079
|View full text |Cite
|
Sign up to set email alerts
|

Association of FPGS genetic polymorphisms with primary retroperitoneal liposarcoma

Abstract: Primary retroperitoneal liposarcoma is generally regarded as a genetic disorder. We have retrospectively genotyped 8 single nucleotide polymorphisms (SNPs) in 6 candidate genes (MDM2, CDK4, CDC27, FPGS, IGFN1, and PRAMEF13) in 138 patients and 131 healthy control subjects to evaluate the effects of genetic factors on individual susceptibility to primary retroperitoneal liposarcoma in Chinese population. Three SNPs (rs2870820, rs1695147, rs3730536) of MDM2 showed significant differences in single-loci genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Following complete resection of primary retroperitoneal liposarcoma, 50% of welldifferentiated and 80% of dedifferentiated tumors recur within 5 years (30,31). Miao et al reported an association of folylpolyglutamate synthetase (FPGS) rs10760502 polymorphism with increased risk for primary retroperitoneal liposarcoma, and suggested that folate supplementation might be useful in decreasing tumorigenesis and preventing postoperative tumor recurrence (32).…”
Section: Discussionmentioning
confidence: 99%
“…Following complete resection of primary retroperitoneal liposarcoma, 50% of welldifferentiated and 80% of dedifferentiated tumors recur within 5 years (30,31). Miao et al reported an association of folylpolyglutamate synthetase (FPGS) rs10760502 polymorphism with increased risk for primary retroperitoneal liposarcoma, and suggested that folate supplementation might be useful in decreasing tumorigenesis and preventing postoperative tumor recurrence (32).…”
Section: Discussionmentioning
confidence: 99%
“…During muscle denervation IGFN1 is substantially upregulated leading to the down-regulation of protein synthesis via eEF1A interaction [ 1 ]. In Chinese population, IGFN1 is associated with susceptibility to Primary retroperitoneal liposarcoma [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…With basic and clinical research, some promising research results and treatment models have emerged. Systemic treatment methods, such as chemotherapy, molecular targeted therapy and immunotherapy ( 24 ) and radiotherapy ( 25 ) have been applied in clinical practice. Radiotherapy exerts significantly different effects on various pathological types of RPLS and may improve local control of patients with WDLPS and G1-2 DDLPS ( 4 ).…”
Section: Discussionmentioning
confidence: 99%